(untitled) (TAJ: Journal of Teachers Association, 2010)
50 patients of chronic ITP were registered in Hematology Department, BSMMU, Dhaka. During this study period (1 yr.) among 50 patients 30 (60 %) were female & 20 (40%) were male. 56% patients were belong to 21- 40 yrs & 32% were between 15- 20 yrs. In this study 50 patients were selected who are refractory to corticosteroid, azathioprine, and cyclophosphamide but none were splenectomized. Patients were above 15 yrs. and have long history of ITP (2 yrs). Out of 50, 48 patients treated with danazol for 12 wks (200- 600mg/day). Patients were followed up on day 7 & 4 wkly up to 12 wks for platelet count, bleeding manifestation & toxicities. Treatment was started to 50 selected patient but 2 patients discontinued the therapy after first dose and remaining 48 patients were completed the therapy. After starting of danazol on day 7, response rate was 79.2% (platelet count raised in 38 patients out of 48 ).On 4th week follow up, 25% (12 patients) achieved (CR) complete remission ( platelet count ≥ 1,50,000/cmm), 62.5% (30 patients) achieved (PR) partial remission( platelet count ≥ 50,000- <1,50,000/cmm) and 6 had no response at all. On 8th week, 7 patients remained in CR (14.6%), 5 in relapsed remained in partial remission. 14.5% (7) patients remained in CR, 10.4% (5) in relapsed remained in partial remission on 12th week. Overall result out of 50 patients (2 excluded who were not attended for follow up & 6 were not responded at all) CR 14.5% (7 patients), PR 72.9% (35 patients).It is cleared from this study & supported by other studies that danazol promptly raised platelets count within 5-10 days with excellent response (79.2%). DOI: 10.3329/taj.v22i1.5026 TAJ 2009; 22(1): 93-96